Cirolana sp SALAH SATU ENDOPARASIT DI DANAU SINGKARAK SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2011)
This written indentification is about endo paracit in Singkaraklake. The specific namely is Cirolana sp which has attacked Hampala sp(sasau) in gill net. This paracit attack anather fish there. It could be seenfrom caring fish floating net in singkarak lake. Because of this paracit, thefarmer can not explore the potential of Singkarak lake in growing thefloating net fish.3